2007
DOI: 10.1590/2175-7860200758204
|View full text |Cite
|
Sign up to set email alerts
|

A synopsis of the genus Poecilanthe (Leguminosae, Papilionoideae, Brongniartieae)

Abstract: RESUMO(Sinopse do gênero Poecilanthe (Leguminosae, Papilionoideae, Brongniartieae)) Este trabalho apresenta um tratamento sintético para as 10 espécies do gênero Poecilanthe (P. amazonica, P. effusa, P. falcata, P. grandiflora, P. hostmannii, P. itapuana, P. ovalifolia, P. parviflora, P. subcordata e P. ulei), incluindo uma chave de identificação e a revisão da nomenclatura e distribuição geográfica. Além disso, a delimitação das espécies é brevemente discutida. Desta forma, P. grandiflora e P.falcata são con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The extensive sampling carried out by Meireles (2007) revealed that Poecilanthe in its broadest sense is not monophyletic and should be divided into three genera. Poecilanthe sensu stricto consistently has resting buds present in the leaf axils, leaflets alternate and mostly stipellate, flowers pedicellate in short racemes, or few-branched panicles, the ovary stipitate, 3 -7ovulate and fruits dehiscent and mostly oblong to oblanceolate (suborbicular only in P. parviflora).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The extensive sampling carried out by Meireles (2007) revealed that Poecilanthe in its broadest sense is not monophyletic and should be divided into three genera. Poecilanthe sensu stricto consistently has resting buds present in the leaf axils, leaflets alternate and mostly stipellate, flowers pedicellate in short racemes, or few-branched panicles, the ovary stipitate, 3 -7ovulate and fruits dehiscent and mostly oblong to oblanceolate (suborbicular only in P. parviflora).…”
Section: Discussionmentioning
confidence: 99%
“…Tabaroa is distinguished from Poecilanthe sensu stricto by the absence of resting buds, leaflets opposite and exstipellate, flowers sessile in short, many-branched panicles, the ovary sessile, 2-ovulate, fruits indehiscent and suborbicular. A second Poecilanthe group recognised by Meireles (2007) includes P. effusa (Huber) Ducke and P. ovalifolia Kleinhoonte and is immediately distinguished from Tabaroa by the very elongate, laxly flowered inflorescences, pedicellate flowers, and fruits internally septate due to a proliferation of inter-seminal papery tissue. The third group of Poecilanthe species includes P. amazonica (Ducke) Ducke and P. hostmannii (Benth.)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genus Poecilanthe (Fabaceae, Papilionoideae, Brongniartieae), established by Bentham (1860), comprises ten South American species distributed from Colombia and French Guiana to East Argentina and Uruguay (Meireles & Tozzi, 2007). Poecilanthe species are shrubs or trees occurring in a wide range of habitats, such as flooded and non‐flooded Amazonian forest, Atlantic rain forest, savannah (cerrado) and seasonally dry forests, including caatinga and restinga.…”
Section: Introductionmentioning
confidence: 99%